A scoping review about smoking, smoking cessation and their effects on anti-tuberculosis agents: insights into drug metabolisms, safety, and effectiveness - Bellanca, Carlo Maria; Polosa, Simone Pietro; Augello, Egle; Di Benedetto, Giulia; Burgaletto, Chiara; Cantone, Anna Flavia; Gaudio, Gabriella; Nunnari, Giuseppe; Campagna, Davide; Nailes, Jennifer M.; Shahbaz, Hamza; Tanuwihardja, Reza Kurniawan; et al. (Frontiers in Pharmacology, 2025)
The World Health Organization (WHO) ranks tuberculosis (TB) as one of the top 10 causes of deaths worldwide. Notably, tobacco smoking represents a significant promoting factor in TB progression, being associated with poorer treatment outcomes, delayed conversion to negative smear or culture, and higher dropout rates from treatment plans. Remarkably, high rates of smoking and TB frequently overlaps in the same countries, warranting the need for targeted public health interventions. Prioritising smoking cessation is essential for smokers with TB, as sustained abstinence has been associated with reduced mortality and a more successful cure. This review examines the intricate relationship between cigarette smoking, smoking cessation therapies and anti-TB drugs, focusing on the impact of tobacco smoking compounds on liver detoxifying systems, such as influence of polycyclic aromatic hydrocarbons (PAHs) on hepatic cytochrome P450 (CYP450) enzymes mostly, and on metabolism of antituberculous medications. Integrating smoking cessation and TB treatment programmes must also take into account potential drug-drug interactions between smoking cessation medications and anti-TB drugs, a critical area for patient safety and effective TB management. This review article aims to provide healthcare professionals with the knowledge to better support TB patients who smoke or are intending to quit, to ensure tailored and effective treatment strategies, while highlighting gaps in current research and advocating for further studies to fill these gaps.